Oncolytic immunotherapy: multiple mechanisms of oncolytic peptides to confer anticancer immunity - Xing Huang; Tingbo Liang; Tianyu Tang; Gang Zhang (Journal for ImmunoTherapy of Cancer)
Oncolytic peptides are highly effective on remodeling the tumor microenvironment and potentiating the anticancer immunity through multiple mechanisms, particularly by inducing immunogenic cell death. Intriguingly, a recent study demonstrates that LTX-315, one of the most promising and extensively studied oncolytic peptides, inhibits PD-L1 expression via ATP11B, thus enhancing the effectiveness of cancer immunotherapy by targeting the PD-1/PD-L1 axis. Therefore, this commentary discusses the broad effects and perspectives of oncolytic peptides on anticancer immunity, further highlighting the potential issues and directions of oncolytic peptides in cancer immunotherapy.